PEMANFAATAN GOOGLE MAPS API PADA SISTEM INFORMASI GEOGRAFIS DIREKTORI PERGURUAN TINGGI DI KOTA BENGKULU - Rena Ariyanti; Khairil Khairil; Indra Kanedi (UNIVED Press, 2015)
Geographic Information System (GIS) that technology is an invaluable tool and is essential to store, manipulate, analyze and display back natural conditions with the help of data and spatial attributes. Bengkulu city is a student city in the province of Bengkulu, there are many universities both public and private sector are spread across the city, but not everyone knows about college lay in Bengkulu city, especially the location or the location of the college. The purpose of this research is to create a geographic information system directory of colleges in the city of Bengkulu that can be used by the institution and the community to support the development of education in the city of Bengkulu. Research conducted at the University Dehasen which began in January to February 2015. In this research, data collection is done by using the method of observation, interviews, and literature. From the results of this study indicate that the presence of a geographic information system directory of colleges in the city of Bengkulu, can provide significant benefits for students and new students determines the location and profile of universities in the city of Bengkulu.Keyword: System, Information, Geographic, Google, Maps